(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
The formal attire of female wheelchair users has received increasing attention in design research, particularly in response to unmet needs in professional settings. However, most existing studies focus on casual or adaptive sportswear, leaving a significant gap in exploring clothing suitable for formal contexts. This study proposes a design method for optimising shirt prototypes for wheelchair users, incorporating two key interventions: structural pattern adjustments and fabric innovation. The method was evaluated through interviews with 51 participants. Conventional shirts often fail to accommodate the seated posture, resulting in poor fit, restricted mobility, and discomfort. To address these issues, structural modifications were introduced to the armholes, sleeve caps, and plackets to enhance forward-reaching mobility and improve dressing convenience. Similarly, fabrics suitable for individuals with limited hand dexterity were selected based on thermal-moisture comfort and usability criteria. Subjective evaluations demonstrated that the synergy between structural refinement and fabric selection significantly improved arm mobility and comfort in a seated position. This study offers practical insights for inclusive formal wear design, presenting a method that balances formal attire for female wheelchair users.